EKSPLORASI FENOMENA TECHNOSTRESS DAN DIGITAL BURNOUT: STUDI KASUS BEBAN KERJA DIGITAL PADA KARYAWAN PENGGUNA MEDIA SOSIAL DAN PLATFORM E-COMMERCE - Dina Tariyani; Deby Aisyah Rj Nur; Novi Peramasari (Jurnal Development, 2026)
This study aims to analyze the phenomenon of technostress and digital burnout among employees using social media and e-commerce platforms. The research employs a qualitative descriptive approach with a case study method involving five purposively selected informants. Data were collected through in-depth interviews and analyzed using the Miles and Huberman (1994) model, including data reduction, data display, and conclusion drawing. The results show that high digital workload, real-time response demands, and blurred work-life boundaries are the main factors contributing to technostress. These conditions may lead to digital burnout, characterized by emotional exhaustion, fatigue toward digital activities, and decreased work motivation.